Transforming Hemophilia A Care: Insights into New Therapeutic Options - Iasmina-Maria Iurea; Emilia Severin; Alexandra Matei (Life)
Hemophilia A is a hereditary bleeding disorder characterized by a deficiency in clotting factor VIII, leading to significant morbidity and a reduced quality of life. This review provides an updated overview of the current understanding of hemophilia A, highlighting its genetic underpinnings and advancements in treatment strategies. A literature review was conducted using various available databases. Relevant studies on hemophilia A, covering genetics and treatment options, were selected and summarized. Recent developments in gene therapy are discussed, showcasing their potential to offer long-term solutions and reduce the burden of treatment. Additionally, the review addresses global disparities in care and policy implications, emphasizing the need for comprehensive healthcare frameworks to improve outcomes for individuals living with hemophilia A worldwide. By synthesizing recent findings and insights, this review aims to inform clinicians and policymakers about the evolving landscape of hemophilia A management and the necessity for equitable access to care.